Blood donation practice and its associated factors among Polish population: secondary data analysis - Siekierska, Barbara; Tomaszek, Lucyna; Kurleto, Paulina; Turkanik, Edyta; Mędrzycka-Dąbrowska, Wioletta (Frontiers in Public Health, 2023)
Introduction Blood transfusion is an intervention widely used in therapeutics (e.g., in the perioperative period), thus, knowledge about factors associated with blood donation is important. The aim of this study was to investigate the impact of sociodemographic factors, personal values and life satisfaction on blood donation in Poland. Methods Secondary analysis of data. A multiple logistic regression was carried out to assess the relationship between sociodemographic factors, life satisfaction (Satisfaction with Life Scale), personal values (Personal Values List) and blood donation. Results Of the 770 respondents aged 18–65 years, 262 respondents (34%) donated blood at least once in their lives. Respondents who believed that blood donation is safe (OR = 1.71; Cl95%: 1.20 to 2.43), were male (OR = 1.47; Cl95%: 1.26 to 1.72), married (OR = 1.31; Cl95%: 1.11 to 1.54) and those with high school education (OR = 0.81; Cl95%: 0.66 to 0.99) were more often blood donors. Conclusion Perceived blood donation safety and sociodemographic factors such as gender, marital status, and education level may influence blood donation. Health education is necessary to increase knowledge and shape positive attitudes toward blood donation among the society.